Effect of Neti Kriya on Common Cold Symptoms in Healthy Yoga Student Volunteers: An Interventional Study - Murugesan , R.; Ketheeswaran , K.; Tiroumourugane, K. (Journal of Neonatal Surgery, 2025)
Background: The common cold is a frequent upper respiratory condition that affects daily functioning and quality of life. Neti Kriya, a traditional yogic nasal cleansing technique, is believed to promote nasal hygiene and reduce upper respiratory symptoms; however, empirical evidence supporting its effectiveness remains limited. Objective: To evaluate the effect of regular Neti Kriya practice on the severity and duration of common cold symptoms in healthy yoga student volunteers. Methods: This prospective interventional study was conducted among 80 healthy yoga students aged 18–35 years. Participants practiced Neti Kriya daily for four weeks using isotonic saline. Common cold symptoms were assessed at baseline and weekly during the intervention using the Wisconsin Upper Respiratory Symptom Survey (WURSS-21). Data were analyzed using repeated measures ANOVA and paired t-tests to determine changes in symptom severity and duration. Results: A significant reduction in mean total WURSS-21 scores was observed from baseline to the end of the intervention (p < 0.001), indicating decreased symptom severity. Participants who developed common cold episodes during the study reported a significantly shorter duration of symptoms compared to pre-intervention estimates (p < 0.001). Improvements were particularly noted in nasal congestion, sneezing, and sore throat. No serious adverse effects were reported, indicating good tolerability of the intervention. Conclusion: Regular practice of Neti Kriya significantly reduced the severity and duration of common cold symptoms among healthy yoga student volunteers. These findings suggest that Neti Kriya may serve as a safe and effective complementary approach for managing common cold symptoms. Further randomized controlled trials are recommended to confirm these results.